Protocol to assess risk of venous thromboembolism associated with use of hormone replacement therapy in real world settings: two nested case-control studies in primary care - Vinogradova, Yana; Coupland, Carol; Mustafa, Mohammed; Hippisley-Cox, Julia (University of Nottingham, 2018)
Hormone replacement therapy (HRT) is used to help women suffering from menopausal symptoms. Although effective, the therapy may have a rare but serious side effect – an increased risk of venous thromboembolism (VTE). Previous studies have not been powerful enough to investigate the risks associated with different types of HRT. The proposed nested case-control study aims to fill this gap. Women diagnosed with VTE between 1998 and 2017 will be matched to 5 controls by age, practice and calendar year. Exposure to each type of HRT will be defined as at least one prescription for that HRT in the year before the index date (date of diagnosis of VTE or equivalent date in matched controls). Conditional logistic regression will be used to assess the risks associated with the different types of oestrogen and progestogen. The effects of duration, length of any gap since last use and method of application will be analysed for the most common types of HRT.